2013
DOI: 10.5194/essd-5-109-2013
|View full text |Cite
|
Sign up to set email alerts
|

The MAREDAT global database of high performance liquid chromatography marine pigment measurements

Abstract: Abstract.A global pigment database consisting of 35 634 pigment suites measured by high performance liquid chromatography was assembled in support of the MARine Ecosytem DATa (MAREDAT) initiative. These data originate from 136 field surveys within the global ocean, were solicited from investigators and databases, compiled, and then quality controlled. Nearly one quarter of the data originates from the Laboratoire d'Océanographie de Villefranche (LOV), with an additional 17 % and 19 % stemming from the US JGOFS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Although detailed information on the taxonomic and size structure of ship-based experiments was lacking for several of the samples included in this data set, more recent studies include some measure of phytoplankton community structure, whether it be from use of pigment markers, size fraction of pigment and/or productivity, or cell counts. As information on the global distribution of key phytoplankton groups is becoming available from global studies of phytoplankton pigment markers and flow cytometric counts (Buitenhuis et al, 2012;Peloquin et al, 2013;Swan et al, 2015), links between phytoplankton biogeography and large-scale pattern in photophysiology as revealed through the P-E parameters may be explored. Although there is a question as to what the standard indices of community structure should be that can help account for community-based variation in the photophysiological parameters across oceanographic data sets (Bracher et al, 2017), it is likely that information on gross community structure alone will not account for a large fraction of the variability in P-E parameters, especially across regions or seasons with different environmental forcing (Bouman et al, 2005;Smith Jr. and Donaldson, 2015) or resident ecotypes (Geider and Osborne, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed information on the taxonomic and size structure of ship-based experiments was lacking for several of the samples included in this data set, more recent studies include some measure of phytoplankton community structure, whether it be from use of pigment markers, size fraction of pigment and/or productivity, or cell counts. As information on the global distribution of key phytoplankton groups is becoming available from global studies of phytoplankton pigment markers and flow cytometric counts (Buitenhuis et al, 2012;Peloquin et al, 2013;Swan et al, 2015), links between phytoplankton biogeography and large-scale pattern in photophysiology as revealed through the P-E parameters may be explored. Although there is a question as to what the standard indices of community structure should be that can help account for community-based variation in the photophysiological parameters across oceanographic data sets (Bracher et al, 2017), it is likely that information on gross community structure alone will not account for a large fraction of the variability in P-E parameters, especially across regions or seasons with different environmental forcing (Bouman et al, 2005;Smith Jr. and Donaldson, 2015) or resident ecotypes (Geider and Osborne, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that future alterations in stratification will also play a role in governing phylogeography within the unicellular cyanobacterial populations. The geographical distribution of Synechococcus extended further northwards than that of Prochlorococcus, illustrating the broader temperature range of Synechococcus (Moore et al 1995;Partensky et al 1999a;Peloquin et al 2013). Recently, it was suggested that the ability of Synechococcus spp.…”
Section: Component Sourcementioning
confidence: 99%
“…While diagnostic pigments have been widely used for validation due to the availability of extensive datasets of HPLC pigments across the global ocean (Peloquin et al, 2013), there are important limitations to consider. The diagnostic pigmentbased approach does not necessarily reflect the true size structure of the phytoplankton communities because some taxonomic groups may spread over a broader size range (e.g., diatoms are typically found in the micro-but could also occur in the nano-size and sometimes in the pico-size classes) and some diagnostic pigments are shared by different taxonomic groups (e.g., fucoxanthin is the main carotenoid of diatoms but may also be found in prymnesiophytes).…”
Section: Algorithm Validationmentioning
confidence: 99%